Land-use change and livelihoods of non-farm households: The role of income from employment in oil palm and rubber in rural Indonesia - Jonida Bou Dib; Vijesh Krishna; Zulkifli Alamsyah; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2018)
Many tropical regions are experiencing massive land-use change that is often characterized by an expansion of oil palm at the expense of forests and more traditional forms of agricultural cropping. While implications of such land-use change for the environment and for local farm households were examined in previous research, possible effects on the livelihoods of non-farm households are not yet well understood. This study analyzes the role of different types of agricultural and non-agricultural employment income for non-farm households in rural Jambi, one of the hotspot regions of Indonesia's recent oil palm boom. Data from a recent survey show that employment in rubber and oil palm are important livelihood components for non-farm households. Employment in oil palm is more lucrative than employment in rubber, so involvement in the oil palm sector as a laborer is positively associated with total household income. Regression models show that whether or not a household works in oil palm is largely determined by factors related to migration background, ethnicity, and the size of the village area grown with this crop. These results suggest that further expansion of the oil palm area will likely benefit non-farm households through gains in employment income. As non-farm households belong to the poorest segments of the rural population, these benefits should not be ignored when designing policies towards sustainable land use.
urn:nbn:de:gbv:7-webdoc-3979-7
Keywords: 330; oil palm; rubber; non-farm households; labor markets; sharecropping; income